Dictionary of children's clothes : 1700s to present - Marshall, Noreen (New York, NY : Victoria and Albert Museum, 2008)
Over the years, children's clothing has witnessed a gradual shift from dressing children to adult requirements, in multiple layers and formal styles, to the booming designer childrenswear market. This dictionary features over 300 garments, from air-raid suits to zouave jackets.
Includes bibliographical references.
boek
Keywords: Children's clothing -- Dictionaries; Children's shoes -- Dictionaries; Dress accessories -- Dictionaries